A Bio-molecular Sensor Based on Optical Weak Measurement. Issue 2 (August 2019) - Xiong, Nian; Wang, Xiangnan; Shi, Lixuan; Xu, Yang; Guan, Tian; He, Yonghong
Abstract: We developed a phase-sensitive sensor based on the optical weak measurement for label-free detection of biomolecular interaction. The weak value amplification system can be implemented in common-path with total internal reflection structure. The phase difference between p and s polarizations caused by biomolecular recognition is measured by the central wavelength shift of the frequency domain weak measurement system. Structure of p and s polarizations in common-path makes system robust and stable. The applicability is illustrated by real-time monitoring interaction of biomolecules.